Review and Prospect of the Measurement Technology of the Thickness of the Liquid Film on the Wall of the Corrugated Plate Dryer - Wang, Bo; Chen, Bowen; Wen, Jiming; Lu, Chuan; Tian, Ruifeng (Frontiers in Energy Research, 2020)
The corrugated plate dryer is an important steam-water separation device in the steam generator in the secondary loop of a light water reactor (LWR). It is essential to understand its steam-water separation mechanism. Most studies have shown that the separation efficiency of the corrugated plate is related to the thickness of the liquid film on the wall of the corrugated plate. The relationship between the thickness of the liquid film and the critical airflow velocity of the corrugated plate has been studied by us. At present, scholars mostly use image method, ultrasonic method and capacitance method to measure the thickness of thin liquid film. We have analyzed the application of these three methods in liquid film thickness measurement. Some important examples are listed. The results show that the capacitance method is recommended for liquid film thickness measurement experiments whereas its accuracy is not particularly high. To pursue the higher accuracy, the image method is recommended. Planar laser-induced fluorescence (PLIF) technology is the first choice among image methods. Ultrasonic method is applicable in the case that the measurement data is large.